An analytical study of linear stability analysis on Soret driven ferrothermohaline convection in a Darcy porous medium with MFD viscosity and coriolis force (Journal of Naval Architecture and Marine Engineering, 2023)
The effect of magnetic field dependent (MFD) viscosity on the onset of Soret driven convection in a ferromagnetic fluid layer heated from below and salted from above saturating rotating porous medium in the presence of vertical magnetic field is investigated theoretically by using Darcy model. The resulting eigenvalue problem is solved using the regular perturbation technique. Both stationary and oscillatory instabilities have been obtained. It is found that increase in MFD viscosity and increase in magnetic Rayleigh number is to delay the onset of ferroconvection, while the nonlinearity of fluid magnetization has no influence on the stability of the system.Journal of Naval Architecture and Marine Engineering Vol 19(2), December, 2022 p. 83-96